The effect of different soil amendment towards bird eyes chili (capsicum frutescens) / Ahmad Firhat Ahmad Lotfi - Ahmad Lotfi, Ahmad Firhat (Faculty of Applied Sciences, 2016)
Soil amendment is one of the important elements to enhance the development of plant. Capsicum frutescens was chosen as their adaptation toward environment and soil is very unlikely or in other words very hard to grow. Capsicum frutescens is known as bird eye chili which encompasses high ascorbic acid and acts as an antioxidant as it helps reduce cancer cell. Biochar, rice straw, baggase, and cow dung are several type of soil amendment reported could encourage the development of the plant. According to the result, biochar having the highest parameter compared to other treatment. The highest mean for height of plant with average 9.358 and the lowest is rice straw with mean 3.323. For number of leaves, biochar had the highest mean with average 5.35 and the lowest is rice straw with mean 1.63. For the length of leaves, biochar had the highest mean with average 3.090 followed by baggase, cow dung, control, and the lowest is rice straw with mean 0.952. The length of root, biochar had the highest mean with average 8.57 and the lowest is rice straw with mean 3.71. During the 6 weeks of this project, there was no chili fruit grew. The chili fruit was expected to grow in week 15. The height of plant, width of leaves, length of leaves, number of leaves, and length of root was measured to differentiate the effect between them. There was a significant different between the treatment. The ability of biochar itself can capable to aid the growth of the plant. On top of that, this project could be one of the benchmark for the entire researcher in such biochar as the soil amendment to save cost and the best amendment for all the crop production.